A ictiofauna do rio Taqueri, alto do rio Paranapanema, Bacia do alto Paraná, distribuição espaço-temporal e aspectos reprodutivos - Nobile, André Batista [UNESP] (2015)
Abstract: Impoundment of rivers cause changes in physical and chemical properties of water, causing compartmentalization of the water dammed in three distinct limnological environments: lotic, transition and lentic. In view of these changes, species with smaller biological demands and/or large reproductive plasticity succeed in the new environment, while species with greater demands and lower reproductive plasticity, tend to have their populations reduced. Thus, the hypothesis of this study were: (i) the compartmentalization of the aquatic environment and the seasonality modulate the spatial distribution of the ichthyofauna? (ii) the compartmentalization of the aquatic environment interferes with the reproductive dynamic of species widely distributed by three compartments? (iii) there are differences in the reproductive dynamic of species with restricted distribution of any of these compartments? Monthly samples were carried out between Sep/12 to Aug/13 in three areas: lotic (A1), transition (A2) and lentic (A3) with the aid of gillnets (meshes 3-14 cm between opposite knots), exposed of the dusk to dawn (approximately 16 hours). In these areas, limnological variables were also measured. The results (i) evidenced the formation of three distinct ichthyofaunistic groups, in which prevailed in the area A1 large migratory species, while in A2 and A3 areas prevailed sedentary or short migration species. The canonical correspondence analysis showed that electrical conductivity, total dissolved solids, transparency and current velocity explain part of these differences. Beta diversity denoted the existence of species turnover between areas and the species richness denoted that A2 has greater richness. Changes caused by seasonality influenced catches in abundance and biomass, taking effect on species richness only in A2. (ii) Astyanax altiparanae and Astyanax fasciatus demonstrated adjusted to all types of environment, with values of ...